PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG PENYELENGGARAAN JENAZAH SESUAI SYARIAT ISLAM - Novi Susanti; Ade Erni Anggraini; Yuniza Tri Putri; Arka Dimas Alfarezi; Yusril Fahlepi (As-Sulthan Journal of Education, 2026)
The management of a corpse is a collective obligation (fardhu kifayah) in Islam that must be performed in accordance with Islamic law. However, in practice, public understanding of proper corpse management remains limited and is often based on inherited traditions rather than religious guidelines. This condition may lead to improper practices in its implementation. This study aims to examine the level of community understanding regarding corpse management and to analyze efforts to improve such understanding through religious education programs. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. The research subjects consisted of community members and local religious leaders. The findings indicate that the educational program significantly improved community understanding. Improvements were observed in knowledge, attitudes, and practical skills. The community demonstrated better understanding of bathing, shrouding, funeral prayer, and burial procedures in accordance with Islamic law.